Quercetin and resveratrol inhibit ferroptosis independently of Nrf2–ARE activation in mouse hippocampal HT22 cells. (February 2023) - Kato, Kosuke; Takahashi, Mayu; Oh-hashi, Kentaro; Ando, Kaori; Hirata, Yoko
Abstract: Oxidative stress is the central pathomechanism in multiple cell death pathways, including ferroptosis, a form of iron-dependent programmed cell death. Various phytochemicals, which include the inducers of the nuclear factor erythroid-2-related factor 2–antioxidant response element (Nrf2–ARE) transcription pathway, prevent ferroptosis. We recently reported that several compounds, such as the potent Nrf2–ARE inducer curcumin, protect mouse hippocampus-derived HT22 cells against ferroptosis independently of Nrf2–ARE activity. The present study characterized the anti-ferroptotic mechanisms of two additional Nrf2–ARE inducers, quercetin and resveratrol. Both compounds prevented erastin- and RSL3-induced ferroptosis of wild-type HT22 cells, and also blocked the exacerbated erastin- and RSL3-induced ferroptosis of Nrf2-knockdown HT22 cells. In both HT22 cells, quercetin and resveratrol blocked erastin- and RSL3-induced elevation in reactive oxygen species. These results suggest that the Nrf2–ARE pathway does protect against ferroptosis, but quercetin and resveratrol act by reducing oxidative stress independently of Nrf2–ARE induction. Quercetin and resveratrol also reduced Fe 2+ concentrations in HT22 cells and in cell-free reactions. Thus, quercetin and resveratrol likely protect against erastin- and RSL3-induced ferroptosis by inhibiting the iron-catalyzed generation of hydroxyl radicals. Unlike quercetin, resveratrol cannot form a chelate structure with Fe 2+ but the density functional theory computation demonstrates that resveratrol can form stable monodentate complexes with the alkene moiety and the electron-rich A ring. Graphical abstract: Image 1 Highlights: Nrf2 activators quercetin and resveratrol inhibit ferroptosis of HT22 cells. Anti-ferroptotic effect of quercetin and resveratrol is maintained under Nrf2 knockdown. Quercetin and resveratrol also inhibit ROS generation and chelate or coordinate ferrous ions. These anti-ferroptotic effects are mediated primarily by iron chelation or coordination.